Pemberian Pakan Kombinasi Tepung Maggot BSF (Hermetia illuens) dan Tepung Daun Tarum (Indigofera sp) Bagi Ikan Lele Dumbo (Clarias gariepinus B) - Syahrizal, Syahrizal; Yulfiperius, Yulfiperius; Ghofur, Muarofah; Safratilofa, Safratilofa; Novianti, Vera (Jurnal Akuakultur Sungai dan Danau, 2024)
Quality feed is a determining factor of production in fish farming.This study aims to determine and analyse the best feed formulation combination of  Meggot Meal Black Soldier Fly (BSF), Hermetia illuens, and Tarum (Indigofera sp) leaf flour  for catfish (Clarias gariepinus B). The treatments in this study were Treatment A. MMB 80% (Maggot Meal Bsf 80%), Treatment B. MMB 60%+TF I20% (Maggot Meal Bsf 60% + Tarum Flour 20%), Treatment C.MMB 40%+TF40% (Maggot Meal Bsf 40% + Tarum Flour 40%), Treatment D.MMB 20%+TF 60% (Maggot Meal BSF 20% + Tarum Flour 60%). There were 12 aquarium containers measuring 50 x 40 x 30 cm. Data were analysed using SPSS 16. The results of parameter analysis of each observation of the test variables gave a significantly different effect (P < 0.05). The best average growth was A. MMB 80% (9.42 grams), followed by B. MMB 60%+TF 20% (7.95 grams), C. MMB 40%+TF 40% (7.36 grams) and D. MMB 40%+TF 40% (7.36 grams). MMB 20%+TF 60% (6.46 grams). The best absolute weight was also in treatment A (6.47±0.22 grams), followed by B (4.91±0.28 grams), C (4.44±0.64 grams) and D (3.81±1.18 grams). For the best length B. (3.67±0.15 cm) and A (2.49±0.14 cm), followed by C (1.74±0.17 cm), D. (1.45±0.18 cm). FC (Best survival in B. (95.55%) and A. (94.44%), respectively C. (77.77%), D. (37.77%). FCR (Feed Convertion Ratio) 1.56±0.12 and EPP (Feed Utilisation Efficiency) 54.88%±3.94 were best and lowest in D. FCR (2.48±0.34) and EPP (6.16%±8.90). Water quality was still in optimal condition for the maintenance of dumbo catfish (Clarias gariepinus B) found temperature 27.91-28.06 oC, pH 7.75- 7.63, DO 6.33-6.51 mg/l, and ammonia 0.550.71 mg/l.